PENDEKATAN HOLISTIK PADA WANITA USIA 54 TAHUN DENGAN DIABETES MELITUS TIPE II DAN OBESE DERAJAT II MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI PUSKESMAS RAJABASA INDAH - Pratiwi, Bella; Ernawati, Tutik (CV. Jasa Sukses Abadi, 2024)
Diabetes Mellitus is one of the degenerative diseases with high prevalence and is increasing every year in Lampung province by 22,345 cases or 1.37%. Obesity is one of the predisposing factors for diabetes mellitus. The prevalence of obesity in the population aged 18 years and over increased from 14.8% to 21.8%. In Lampung province, it was 17.3%. Diabetes mellitus and Obesity must be managed comprehensively which is expected to prevent complications and improve the quality of life of patients. Objective: Implementation of Evidence Based Medicine-based services in patients by identifying risk factors, clinical problems, and patient management based on a patient problem-solving framework with a patient-centered, family-focused, and community-oriented approach. Method: This study is a case report. Primary data was obtained through anamnesis, physical examination and home visits to assess the physical environment. Assessment based on a holistic diagnosis from the beginning, process, and end of the study qualitatively and quantitatively. Results: After the intervention, there was an increase in patient and family knowledge regarding the importance of health care provider check-ups, regular medication consumption, appropriate diet and physical activity patterns for patients with Diabetes Mellitus and Obesity. Conclusion: Holistic management has been carried out with a family doctor approach for Mrs. A, 54 years old with type II Diabetes Mellitus and grade II Obesity which was adjusted based on the initial holistic diagnosis. The intervention has increased patient and family knowledge regarding the importance of health care provider check-ups, regular medication consumption, diet and physical activity patterns as indicated by improvements in the final holistic diagnosis.